Financial Inclusion and Economic Development: Assessing the Impact of Microfinance Institutions - Hartoto, Hartoto; Oktana, Enda; Nobelson, Nobelson; Rianti, Titis Surya Maha (Jurnal Mamangan, 2023)
Financial inclusion is a crucial pillar in promoting sustainable economic development, particularly in rural areas and small-scale communities. In Indonesia, microfinance institutions (MFIs) play a strategic role in expanding access to financial services to groups underserved by formal banking institutions. This study aims to assess the impact of Sharia-based and conventional MFIs on increasing financial inclusion and the economic development of farmers and small businesses in East Lombok Regency, West Nusa Tenggara. The study employed a quantitative approach, collecting data through a survey of 120 respondents who were active MFI customers. Data analysis was conducted using multiple linear regression to measure the relationship between MFI service intensity and indicators of financial inclusion and local economic growth. The results indicate that both Sharia-based and conventional MFIs significantly influence financial inclusion. However, Sharia-based MFIs tend to contribute more to the development of sustainable financial behavior, while conventional MFIs show a direct impact on increasing business income. These findings underscore the importance of strengthening the role of MFIs in local economic development policies, particularly in promoting the welfare of farmers and MSMEs in rural areas.